Exploring Sentiment Analysis to understand Software Crowdsourcing Challenges - M. Melo, Ricardo Rodrigo; S. Machado, Leticia; R.B. de Souza, Cleidson (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais Estendidos do XV Simpósio Brasileiro de Sistemas Colaborativos, 2019)
Companies are increasingly using crowdsourcing to accomplish specific software development tasks. This paper describes the initial results from a exploratory study using sentiment analysis in a software crowdsourcing context from a crowd perspective. We classify the polarity of the messages exchanged in challenge forums. Although there are not applications for sentiment analysis of messages in the software crowdsourcing context, our ultimate goal is to understand how good or bad the crowd is talking about and explore if negative messages can be factors that influence the decrease in motivation, especially among the crowd and if positive sentiments can help to encourage contribution to challenges.